Bangladeshi anglophone literature: an old and evolving tradition - Quayum, Mohammad A.; Hasan, Md. Mahmudul (Asiatic Society of Bangladesh, 2021)
It is significant to note that, as opposed to comparable literary traditions in other regions of the South Asian subcontinent, the Bangladeshi Anglophone literary tradition has arguably the most prolific and distinguished historical origins. Once considered the jewel in the crown of British India, where the country’s capital was located (until 1911) and where the process of European colonisation began, the Bengal region was more exposed to English education during the British period than the other British Indian provinces. The first institution of its kind, the Hindu College in Calcutta was established in 1817 by the joint initiative of the British colonists and the native gentry, led by Raja Ram Mohan Roy (1774-1833), an iconic Renaissance figure who was keen to spread English education among the local population long before Thomas Macaulay’s policy of the Anglicisation of Indian education.4 If we take this historic context into account, then Bangladeshi literature in English can be traced back to the East India Company period, to a time before Macaulay wrote his now infamous Minutes on Indian Education in February 1935 or Bentinck’s English Education Act took effect in March of the same year and can, therefore, be regarded as one of the oldest and most illustrious English-language literary traditions outside the English-speaking world.